Energy-Growth Nexus in Indonesia: Fresh Evidence from Asymmetric Causality Test - Ikhsan, Ikhsan; Fachrurrozi, Kamal; Nasir, Muhammad; Elfiana, Elfiana; Nurjannah, Nurjannah (International Journal of Energy Economics and Policy, 2022)
The purpose of this study is to examine the causality between energy consumption and economic growth with an asymmetric causality approach in Indonesia. Data used from 1971-2014. Asymmetric causality using the Hatemi-J method (2012). Bootstrap simulation is also implemented because the data is not normally distributed and there is volatility to get a more reliable critical value than using asymptotic values. The first finding is that classical causality with Toda-Yamamoto finds no relationship between energy consumption and economic growth in Indonesia. The second finding shows that asymmetric causality shows no relationship between energy consumption and economic growth on a positive cumulative basis. However, the third finding obtained a bidirectional in negative cumulative. It is known that the impact of a decrease in energy consumption is greater on a decrease in economic growth than vice versa. Based on these findings, energy consumption in Indonesia has reached an optimal point so that additional energy consumption does not have an impact on economic growth. However, efforts to stabilize energy and economic growth are urgently needed.